The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jan.14002
|View full text |Cite
|
Sign up to set email alerts
|

Making a career in hospitals: Determinants of registered nurses’ aspirations to become a manager

Abstract: Aim To examine seven determinants of Registered Nurses’ aspirations to become a manager in four Norwegian public hospitals. Background Research evidence shows that nurses submit few applications to management positions. Understanding the determinants that influence nurses’ aspirations to become managers can provide healthcare organizations with important knowledge on the drivers and barriers in recruitment and on the development of nurse managers. Design This study adopted a cross‐sectional web‐based survey de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Without appropriate talent management practices, a healthcare organization's potential to recruit and keep “the best and the brightest nurses and midwives” is impeded (Elkady et al, 2019 , p. 1). Healthcare organizations must therefore ensure their HR plan assists the organizations in acquiring the nursing and midwifery skills they need now and into the future (Haaland et al, 2019 ). Creating a future‐oriented workforce will healthcare organizations deal with the changing complexities of the sector and ensuring a workforce with the specific skills, attitudes and knowledge needed (Paans et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Without appropriate talent management practices, a healthcare organization's potential to recruit and keep “the best and the brightest nurses and midwives” is impeded (Elkady et al, 2019 , p. 1). Healthcare organizations must therefore ensure their HR plan assists the organizations in acquiring the nursing and midwifery skills they need now and into the future (Haaland et al, 2019 ). Creating a future‐oriented workforce will healthcare organizations deal with the changing complexities of the sector and ensuring a workforce with the specific skills, attitudes and knowledge needed (Paans et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the amount of vacant nursing posts on the rise, the risks in terms of reduced patient safety and negative health outcomes are increased. It is therefore necessary for healthcare organizations to work strategically to develop a human resource management policy that ensures that the PLOS ONE organization develops the nursing capabilities it needs now and, in the future, [12]. To date, global crises have showed that skilled workers must be placed in important positions in organization's and then effectively managed for the organization's long-term viability and ability to respond quickly to changing priorities and demands for services [13].…”
Section: Introductionmentioning
confidence: 99%